Impact of the COVID-19 pandemic on orthopedic trauma workload in a London level 1 trauma center: the "golden month": The COVid Emergency Related Trauma and orthopaedics (COVERT) Collaborative - Park, Chang; Sugand, Kapil; Nathwani, Dinesh; Bhattacharya, Rajarshi; Sarraf, Khaled M (Acta orthopaedica, 2020)
Background and purpose - The COVID-19 pandemic has been recognized as an unprecedented global health crisis. This is the first observational study to evaluate its impact on the orthopedic workload in a London level 1 trauma center (i.e., a major trauma center [MTC]) before (2019) and during (2020) the "golden month" post-COVID-19 lockdown. Patients and methods - We performed a longitudinal observational prevalence study of both acute orthopedic trauma referrals, operative and anesthetic casemix for the first "golden" month from March 17, 2020. We compared the data with the same period in 2019. Statistical analyses included median (median absolute deviation), risk and odds ratios, as well as Fisher's exact test to calculate the statistical significance, set at p ≤ 0.05. Results - Acute trauma referrals in the post-COVID period were almost halved compared with 2019, with similar distribution between pediatric and adult patients, requiring a significant 19% more admissions (RR 1.3, OR 2.6, p = 0.003). Hip fractures and polytrauma cases accounted for an additional 11% of the modal number of injuries in 2020, but with 19% reduction in isolated limb injuries that were modal in 2019. Total operative cases fell by a third during the COVID-19 outbreak. There was a decrease of 14% (RR 0.85, OR 0.20, p = 0.006) in aerosol-generating anesthetic techniques used. Interpretation - The impact of the COVID-19 pandemic has led to a decline in the number of acute trauma referrals, admissions (but increased risk and odds ratio), operations, and aerosolizing anesthetic procedures since implementing social distancing and lockdown measures during the "golden month."